2001
DOI: 10.1002/dc.1093
|View full text |Cite
|
Sign up to set email alerts
|

Neural network‐based screening (NNS) in cervical cytology: No need for the light microscope?

Abstract: Neural network-based screening (NNS) of cervical smears can be performed as a so-called "hybrid screening method," in which parts of the cases are additionally studied by light microscope, and it can also be used as "pure" NNS, in which the cytological diagnosis is based only on the digital images, generated by the NNS system. A random enriched sample of 985 cases, in a previous study diagnosed by hybrid NNS, was drawn to be screened by pure NNS. This study population comprised 192 women with (pre)neoplasia of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…[4][5][6][7][8][9] More specially, concerning cytology, these techniques have been applied to various organs, among others stomach, [10][11][12] breast, [13][14][15][16] urinary system, [17][18][19] cervix, [20][21][22][23][24] and thyroid. [25][26][27][28] Classification and Regression Trees (CARTs) are very popular techniques, and have been often used in the past.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] More specially, concerning cytology, these techniques have been applied to various organs, among others stomach, [10][11][12] breast, [13][14][15][16] urinary system, [17][18][19] cervix, [20][21][22][23][24] and thyroid. [25][26][27][28] Classification and Regression Trees (CARTs) are very popular techniques, and have been often used in the past.…”
Section: Introductionmentioning
confidence: 99%
“…12 All slides were of a good-enough quality to be scanned with the neural network scanner. 8 The mean time to scan the thin-layer slides with the scanner was 8 minutes, while it took 15 minutes for conventional slides. 11 The images of the Papspin ® slides had, with-out exception, a clear background, resulting in high contrast between the diagnostic elements.…”
Section: Discussionmentioning
confidence: 99%
“…After staining the slides were coverslipped with plastic film and scanned with a neural network scanner, formerly known as PAPNET. 8 …”
Section: Thin-layer Methodsmentioning
confidence: 99%
“…13 Since the introduction of the PAPNET testing system in the Leiden Laboratory, which uses neural network-based technology in combination with light microscopy, the balance between correctly diagnosed cases and "false-negatives" has been fully optimized. 8 This system is not commercially available in the United States. It is not unlikely that, in due course, an alternative, but comparable neural network based system will be available for use, not only within, but also outside, the United States.…”
Section: Discussionmentioning
confidence: 99%
“…7 Using this screening system, smears previously reported as negative can be reanalyzed for missed cancer cells or cancerous material or for additional information of background features such as blood. 8 In the context of bloody smears, a variety of studies have found that with progression of cervical dysplasia, mean vessel density increases in the underlying submucosal connective tissue of the cervix. Thus, the onset of angiogenesis appears to be an early event in malignancy-related changes of the cervix.…”
Section: Introductionmentioning
confidence: 99%